Struktur Komunitas Alga Perifiton Sungai dalam Gua Batu Asahan di Sumpur Kudus Kabupaten Sijunjung Sumatera Barat - Izmiarti Izmiarti (Universitas Andalas, 2019)
The cave ecosystem has a unique environment because it receives minimal sunlight and does not even get sunlight at all. Dark conditions in the cave will affect producers such as periphyton algae that live in rivers in caves that need sunlight for photosynthesis. This study aims to determine the periphyton community structure in the river in the Batu Asahan Cave in Sumpur Kudus, Sijunjung District, West Sumatra. This research held in August 2016. The research was carried out by survey method at 3 stations: bright, dim and dark zones. The results showed that periphyton were found as many as 22 species classified as Bacillariophycea 13 species, Cyanophyceae 5 species, Chlorophyceae and Euglenophyceae each of 2 species. Based on the number of individuals Bascillariophyceae 67.0%, Cyanophyceae 24.49%, Chlorophyceae 4.79% and Euglenophyceae 3.72%. Population density in each zone was low, ranges from 1.26 - 2.82 ind / cm2. The dominant species vary in each zone which is the highest shown by Synedra ulna (Bacillariophyceae) and Oscillatoria tenuis (Cyanophyceae). Diversity index ranging from 2.11-2.47 is not significantly different between zones, indicating the quality of clean water. The equitability index was high (E = 0.88-0.96) show the populations in the community evenly. Similarity index between zones was low (C = 25 - 56%). Fisicochemical factors of water indicate the quality of clean water supports the life of periphyton algae in the river.